Peran Pendidikan Agama Islam dalam Pembinaan Moral Siswa di Lingkungan Sekolah Multikultural - Fitria Meilinda; Dian Jelita; Novita Rahmayanti; Shelda Tenri Bela; Siti Zulaiha (JMiE (Journal of Management in Education), 2024)
This study examines the role of Islamic Religious Education (PAI) in strengthening moral development among students in the multicultural environment of SMP Negeri 15 Bengkulu City. The objectives are to analyze students’ moral issues, describe moral development strategies based on PAI, and identify supporting and inhibiting factors in its implementation. The research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings indicate that PAI significantly contributes to moral development through dialogical learning, contextual material delivery, teacher role modeling, and structured religious programs such as congregational prayers and daily worship practices. The multicultural environment also fosters tolerance and respect for diversity. Nevertheless, challenges remain, including digital behavior, cultural differences, and limited parental involvement. Overall, PAI plays a strategic role in shaping students’ moral awareness, discipline, and social harmony in a multicultural school setting.